How does group antenatal care function within a caseload midwifery model? A critical ethnographic analysis. Issue 5 (May 2015) - Allen, J.; Kildea, S.; Stapleton, H.
Abstract: Background: caseload midwifery and CenteringPregnancy™ (a form of group antenatal care) are two models of maternity care that are separately associated with better clinical outcomes, maternal satisfaction scores and positive experiences compared to standard care. One study reported exclusively on younger women׳s experiences of caseload midwifery; none described younger women׳s experiences of group antenatal care. We retrieved no studies on the experiences of women who received a combination of caseload midwifery and group antenatal care. Objective: examine younger women׳s experiences of caseload midwifery in a setting that incorporates group antenatal care. Design: a critical, focused ethnographic approach. Setting: the study was conducted in an Australian hospital and its associated community venue from 2011 to 2013. Participants: purposive sampling of younger (19–22 years) pregnant and postnatal women ( n =10) and the caseload midwives ( n =4) who provided group antenatal care within one midwifery group practice. Methods: separate focus group interviews with women and caseload midwives, observations of the setting and delivery of group antenatal care, and examination of selected documents. Thematic analyses of the women׳s accounts have been given primary significance. Coded segments of the midwives interview data, field notes and documents were used to compare and contrast within these themes. Findings: we report on women׳s first encounters with the group, and their interactions with peers and midwives. The group setting minimised the opportunity for the women and midwives to get to know each other. Conclusions: this study challenges the practice of combining group antenatal care with caseload midwifery and recommends further research.